SPECIFICS OF TECHNICAL PROTECTION OF INFORMATION: SAFETY CONTEXTS - Vivchar, Oksana Ivanivna; Shatarskyi, Artur Yaremovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article conducts a comprehensive study of specifics the technical protection of information by business entities in order to ensure security conditions. On the basis of which the identification the components of information system at the present stage of development is carried out.